The impact of a conducive work environment on improving employee performance - Santoso, Anton Budi; Oktafien, Shinta (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
This research aimed to assess the influence of a conducive work environment on enhancing employee performance at PT. Astra Honda Motor Sampurna, encompassing a population of 32 employees. The study employed a quantitative research approach, utilizing a saturated sampling method, where the entire population served as the sample. Data processing and analysis involved descriptive statistics, research instrument testing (validity, reliability, and classical assumption tests), simple regression analysis, and hypothesis testing (t and F tests) conducted through SPSS version 23.0.Results indicated a positive and significant impact of the work environment on improving employee performance at PT. Astra Honda Motor Sampurna. Consequently, the research concluded that the work environment plays a crucial role in influencing employee performance. Organizations capable of fostering a safe and comfortable work environment can witness enhanced employee performance. Conversely, if the work environment is perceived as less conducive, it may lead to suboptimal employee performance. This underscores the importance of creating a supportive and positive workplace atmosphere to maximize employee potential and productivity.